2013
DOI: 10.1103/physrevc.88.064313
|View full text |Cite
|
Sign up to set email alerts
|

Isoscalar giant resonance strengths in32S and possible excitation of superdeformed and28Si+et al.

Abstract: Isoscalar giant resonances and low spin states in 32 S have been measured with inelastic α scattering at extremely forward angles including zero degrees at E α = 386 MeV. By applying the multipole decomposition analysis, various excited states are classified according to their spin and parities (J π ), and are discussed in relation to the super deformed and 28 Si + α cluster bands.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…7. The sum of these components in the energy region [15][16][17][18][19][20][21][22][23][24][25] MeV is in reasonable agreement with the data. Again, comparison of data with the spherical and deformed ground-state microscopic calculations clearly indicates that ISGQR strength fragmentation in 24 Mg corresponds to a prolate-deformed ground state.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…7. The sum of these components in the energy region [15][16][17][18][19][20][21][22][23][24][25] MeV is in reasonable agreement with the data. Again, comparison of data with the spherical and deformed ground-state microscopic calculations clearly indicates that ISGQR strength fragmentation in 24 Mg corresponds to a prolate-deformed ground state.…”
Section: Discussionsupporting
confidence: 78%
“…These are understood in terms of K-splitting: microscopic calculations based on quasiparticle random-phase approximation (QRPA) [11], for example, predict K-splitting of the multipole strength even in light deformed nuclei such as 24 Mg [12,13]. Identification of full giant-resonance strengths in the lighter-mass nuclei (A < 60) has generally been a chal-lenge due to fragmentation of the strength [14][15][16][17][18][19][20][21][22], significant overlap of giant resonance strengths for L ≤2, uncertainties in the extraction of the strength distributions, and overlap of the multipole strength with other direct processes (knock-out/quasi-free processes, for example). The light nuclei, in particular the deformed ones such as 24 Mg and 28 Si, provide a vital testing ground for the aforementioned QRPA and deformed Hartree-FockBogoliubov (HFB) calculations [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Isoscalar giant monopole resonances (ISGMRs) and isoscalar giant dipole resonances (ISGDR) are extensively examined by the MDA for the inelastic α scattering [1][2][3][4][5][6][7][8][9][10]. The ISGMR and ISGDR strength distributions were successfully extracted from continuous excitation-energy spectra by the MDA.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, its strength distributions measured for light nuclei [4][5][6]10,11,13,35,36] show the existence of the sharp resonances with enhanced strengths at relatively small excitation energies well below the giant resonance. In a recent experimental study [35], the observed low-lying resonances in 32 S are conjectured to be the α + 28 Si cluster states, because of their enhanced IS dipole transition strength from the ground state. Very recently, Kanada-En'yo also discussed the enhancement of the IS dipole transition strength of the α cluster states in 12 C based on a theoretical calculation [56].…”
Section: Introductionmentioning
confidence: 99%
“…This finding boosted the studies of the cluster states by using the monopole transition as a probe. In these days, various cluster states in stable and unstable nuclei [33][34][35][36][37][38][39][40] are discussed on the basis of their enhanced monopole strengths.…”
Section: Introductionmentioning
confidence: 99%